The high-resolution structure of the extracellular domain of human CD69 using a novel polymer - Kolenko, Petr; Skálová, Tereza; Vanek, Ondrej; Stepánková, Andrea; Dusková, Jarmila; Hasek, Jindrich; Bezouska, Karel; Dohnálek, Jan (Acta crystallographica. Section F, Structural biology and crystallization communications, 2009)
The structure of the extracellular domain of human CD69 has been determined by single-crystal X-ray diffraction. The structure refined to 1.37 A resolution provides further details of the overall structure and the asymmetric interface between the monomers in the native dimer. The protein was crystallized using di[poly(ethylene glycol)] adipate, which also served as a cryoprotectant. This is the first report of a crystal structure determined using crystals grown with this polymer.
Keywords: Crystallography, X-Ray; diferenciační antigeny T-lymfocytů; rekombinantní proteiny; Lectins, C-Type; Polymers; Protein Conformation; Models, Molecular; molekulární modely; Humans; Recombinant Proteins; lektiny typu C; polymery; Antigens, Differentiation, T-Lymphocyte; Antigens, CD; CD antigeny; lidé; konformace proteinů; krystalografie rentgenová